2019
DOI: 10.1177/1715163518816726
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative exploration of the education and skill needs of community pharmacists in Saskatoon concerning substance use disorder

Abstract: Background: Identifying the skills and educational needs of community pharmacists concerning addiction is critical to improving the services provided for people who suffer from addiction disease (PWsAD). Methods: Eleven one-to-one semi-structured interviews were conducted with community pharmacists practising in the saskatoon Health region, canada. the interviews were recorded and transcribed verbatim and verified with the participants. thematic analysis was employed to analyze the transcripts. Results: Four m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…The ndings of the study suggested that the participants' experiences with community pharmacists are generally negative, with many interactions lacking proper counseling and support. Similar to other studies, lack of pharmacist time, stigma(39), lack of privacy (40), and need for additional education for pharmacists (24) were mentioned by participants among the barriers to accessing care in a community pharmacy setting.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The ndings of the study suggested that the participants' experiences with community pharmacists are generally negative, with many interactions lacking proper counseling and support. Similar to other studies, lack of pharmacist time, stigma(39), lack of privacy (40), and need for additional education for pharmacists (24) were mentioned by participants among the barriers to accessing care in a community pharmacy setting.…”
Section: Discussionsupporting
confidence: 79%
“…Similar to other pharmacy clients, participants were willing to explore and access the extended services pharmacists can offer beyond the traditional model of dispensing medications (42,77). Paradoxically, pharmacists in Saskatoon expressed a great deal of caution and hesitation when approaching suspected SUD patients to offer help (24). In fact, community pharmacists perceived that it might be offensive to the clients to initiate a discussion in relation to substance use (24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study found that pharmacists are willing to be educators for the public and provide preventative services for clients who use substances [ 15 ]. Some pharmacists also recognized opportunities in daily practice to intervene and help clients in the early stages of SUDs [ 16 ]. On the other hand, pharmacy customers with risky alcohol consumption had a positive attitude regarding utilizing alcohol screening services provided by their regular community pharmacists [ 17 ].…”
Section: Introductionmentioning
confidence: 99%